2004
DOI: 10.1111/j.0309-0167.2004.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tie‐1 and 2 receptors, and angiopoietin‐1, 2 and 4 in gastric carcinoma; immunohistochemical analyses and correlation with clinicopathological factors

Abstract: Ties and Angs were highly expressed in human gastric adenocarcinoma cells. These findings suggest that the Tie-Ang receptor-ligand complex is one of the factors involved in the cellular differentiation and progression of human gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
(34 reference statements)
1
16
1
1
Order By: Relevance
“…In contrast, overexpression of ANG-2 in hepatomas, gliomas, and colorectal and gastric carcinomas was found to enhance angiogenesis and augment tumor malignancy (46,(53)(54)(55)(56). Furthermore, strong correlation of ANG-2 with ANG-1 in neuroblastoma (57), gliomas (14,35), breast and prostate carcinomas (58), hepatocellular carcinoma (59), non -small cell lung carcinomas (60,61), and gastric adenocarcinoma (62) has been associated with aggressive tumor growth.…”
Section: Ang-2mentioning
confidence: 99%
“…In contrast, overexpression of ANG-2 in hepatomas, gliomas, and colorectal and gastric carcinomas was found to enhance angiogenesis and augment tumor malignancy (46,(53)(54)(55)(56). Furthermore, strong correlation of ANG-2 with ANG-1 in neuroblastoma (57), gliomas (14,35), breast and prostate carcinomas (58), hepatocellular carcinoma (59), non -small cell lung carcinomas (60,61), and gastric adenocarcinoma (62) has been associated with aggressive tumor growth.…”
Section: Ang-2mentioning
confidence: 99%
“…A receptor-mediated response is likely given that Tie2 expression was induced by hyperoxia 59 and Tie2 has been detected on normal and transformed epithelial cells. [66][67][68] Furthermore, we detected Tie2 mRNA in the MLE cells used for our in vitro studies. 59 Importantly, we found Ang2-mediated hyperoxia-induced increases in initiator and effector caspases, namely caspase-3, -8 and -9.…”
Section: Angiopoietin 2 and Hali In Animal Modelsmentioning
confidence: 99%
“…StrongevidencefortheinvolvementoftheIAPfamilyin theregulationoftumorprogression,cellulargrowth,anddifferentiation has been found [10][11][12]. Previous studies have shown that survivin or livin expression is associated with tumorigenesis and metastasis in epithelial tumors including CRC.…”
Section: Introductionmentioning
confidence: 99%